Paleoecological observations of the corals reefs of the upper Tortonian between Viannos - Ierapetra provinces (SE Crete) - MARCOPOULOU - DIACANTONI, A. (Bulletin of the Geological Society of Greece, 2018)
The fossilized association as well as the pétrographie material coming from a sedimentary basin (ca. 30 km2) situated at the SE part of Crete, between the Provinces Viannos and Ierapetra are studied. The fossiliferous regions are in the area of the villages Myrtos, Mournies and Gdochia. Among an important number of fossils (154 taxons): 83 Foraminifers, 19 Bivalves, 24 Gastropods, Ostracods, 3 Echinoids, 13 Anthozoans, 1 Scaphopods, 6 Bryozoans, 2 Algues etc. there are some characteristic species of the Upper Tortonian age- especially Gl. obliquus extremus (zone of G. numerosa)- found in these sediments known up today generally as Miocene. The Tortonian age are based also on the occurrence of the species: Spondylus concentricus, Chlamys submalvinea, Chlamys solarium, Gryphaea gingensis, Gryphaea gryphoides crassissima, Turritella formata pseudoimbricata, Terebralia bidentata bidentata, Pontes collegniana, Palaeoplesiastraea desmoulinsi, Tarbellastraea carryensis, Thegioastraea rosacea etc. Based on the faunal and floral association and their morphofunctional analysis, their conditions of existence etc. the author attempts to interpret the paleoenvironmental conditions during the timespan of the Upper Tortonian, like as patch reefs or micro-atolls and lagoons.